A randomized phase III study comparing continuation and discontinuation of PD-1 pathway inhibitors for patients with advanced non-small-cell lung cancer (JCOG1701, SAVE study). (19th May 2020) - Nomura, Shogo; Goto, Yasushi; Mizutani, Tomonori; Kataoka, Tomoko; Kawai, Shoko; Okuma, Yusuke; Murakami, Haruyasu; Tanaka, Kentaro; Ohe, Yuichiro
Abstract: The development of PD-1 pathway inhibitors has dramatically altered the treatment of advanced/recurrent non-small-cell lung cancer patients. However, the prognostic significance of their ongoing usage is controversial, especially for patients who have not progressed for a period of time. If discontinuation has no negative impact on survival, suspension may reduce side effects from toxicity and help alleviate the economic burdens on health insurance systems and patients. This randomized controlled trial enrolls patients who have responded well to PD-1 pathway inhibitors for >12 months. The aim is to confirm the non-inferiority of discontinuation of PD-1 pathway inhibitors, relative to continuation, in terms of overall survival. A total of 216 patients will be enrolled over 3 years. This trial has been registered in the Japan Registry for Clinical Trials as jRCT1031190032 (https://jrct.niph.go.jp/ ). An ancillary study examining the prognostic and predictive role of circulating tumor DNA using Guardant360 ® is planned. Abstract : This phase III trial aims to confirm the non-inferiority of discontinuation versus continuation of treatment with immune checkpoint inhibitors, including PD-1 pathway inhibitors, for advanced/recurrent non-small-cell lung patients.